Review Article: Multispecies Biofilms an Overview - Hamdi, Nagham Maad; Tawfeeq, Heba Khaleel; Ahmed, Suaad Ali (Journal for Research in Applied Sciences and Biotechnology, 2023)
Microorganisms frequently form structured communities enclosed within copious amounts of extracellular polymeric substance (EPS), known as biofilms. These biofilm formations are widespread and can be found on surfaces such as plants, soil, the human body, and medical implants. In natural settings, biofilms consist of multiple species, and these multi-species biofilms (MSBs) are known to enhance resistance against physical and chemical challenges. Additionally, MSBs exhibit greater biomass due to synergistic interactions compared to their single-species counterparts. The development of MSBs involves several stages, including initial colonization, incorporation into EPS, attachment of subsequent species to pioneers, and eventual biofilm dispersal as the biofilm matures. Cooperation and competition within MSBs play pivotal roles in shaping the overall structure of these microbial communities. Various mechanisms have been proposed to elucidate how MSBs achieve significantly higher antimicrobial resistance levels, often exceeding those of planktonic counterparts by orders of magnitude.